Facies y paleoambiente de la Formación Santa Rosita en las regiones de Pantipampa y Rodeo Colorado (Departamento Iruya, Provincia de Salta), Cordillera Oriental, Argentina - Esteban, Susana Beatriz (2021)
The Santa Rosita Formation (late Furongian-Tremadocian) is a classic unit in the Lower Paleozoic of the Cordillera Oriental, northwestern Argentina, that represents a wide variety of sedimentary environments. Sedimentological and paleoenviromental information from the middle part of the formation (Kainella meridionalis, K. teiichii, and Bienvillia tetragonalis Zones; lower to middle Tremadocian) at Pantipampa and Rodeo Colorado localities (Iruya area, Salta Province), is provided herein. Based on lithology, bed geometry, features of the internal lamination, degree of bioturbation and the record of bioclastic concentrations, four facies are recognized in the sections studied. The succession is interpreted as having formed in a wave-dominated shelf with storm activity influence. Background sedimentation was punctuated by storm deposition in an upper offshore to offshore-transition setting.